Analisis Kualitas Air Tanah Dangkal dengan Parameter Fisik- Kimia Di Kota Dili, Timor – Leste - Ximenes, Livio Xavier; Kusuma, Maritha Nilam (Teknik Lingkungan, Institut Teknologi Adhi Tama Surabaya, 2024)
Dili City is located on the northern coast of Timor Island. Geologically, the interaction between the Australian and Eurasian tectonic plates has formed the Dili Basin. Most residents of Dili still rely on well water or groundwater to meet their daily water needs without further assessment of the suitability of the groundwater. Therefore, the researcher tested the quality of groundwater according to its physicochemical parameters. This research employed laboratory observation methods to determine the concentration values in the groundwater of the Dili area and compare them with several regulations regarding the standards of raw water quality. The results of this study showed that the Dili area had various concentrations of pH, TDS, DO, and salinity, with the highest values of 6.14, 598 ppm, 183 ppm, and 675 ppt, respectively. The groundwater quality in the Dili area fell into the hazardous category, as the salinity concentration was 2.1 ppt and DO was 6 ppm.